PENGARUH VIDEO TUTORIAL PENYETELAN CELAH KATUP ENGINE TERHADAP HASIL BELAJAR SISWA KELAS XI TKR DALAM MATA PELAJARAN PRAKTIK MOTOR BAKAR DI SMK NAGARA NGAWI TAHUN AJARAN 2013/2014 - Nasrudin, Muchtar (Jurnal Nosel, 2014)
The purpose of study to determine the tutorials video learning method to produce better result than the conventional methods in the practice of Fuel Motor subjects in 11th  TKR class OF SMK Nagara Ngawi academic year 2013/2014.This research includes experimental research . Forms and researches strategy which used is a comparison between conventional learning with Tutorial Video learning innovation by using a control class population sample and experimental class. Total population in this study are 70 IIth students of Vehicle Engineering subjects of SMK Ngawi Nagara, consists of 2 class of automotive  in the  IIth grade (TKR 1 and 2 IIth class) on the fuel motor subjects in the academic year of 2013/2014. Samples are taken by a sampling total technique, the number samples are 70 students of IIth class Engineering Vehicle . Data collection technique is the competency test method. Data analysis techniques in this study is using normality test, homogeneity and hypotheses test by using the mean difference test two right- hand t test with significance level of 5 %.The results of this study shows that the effectiveness of the tutorial Video learning model of slit valve adjustment in improving student learning shows a significant difference with the conventional model of learning, the result learning of experimental group increased, and the average estimate of the results learning 75-95, the average study group experimental results of the 85.69. The results of the calculation of the difference average obtained t value = 84.024 > t table = 2.03. While the control group also increased, the average estimate of 60-80, the results average of the control study group 66.66. it shows that the result learning which used learning tutorial Video models of slit valve adjustment is better than using the conventional model. The conclusions of this study is the outcomes learning of the tutorial tutuorial video learning model of slit valve adjustment is better than the use of conventional methods It can be seen in the average value of a class that uses a learning model slit valve adjustment tutorial video turned out to greater outcomes learning is 85.69 while the results obtained by the conventional method of learning for 66.66. This implies that the learning model by using the tutorials Video learning of slit valve adjustment is more effective because the video stimulate the interest students, so that students are more active.